IMPLEMENTASI TAMBAHAN PENGHASILAN BERDASARKAN BEBAN KERJA DALAM PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL (STUDI PADA KANTOR WALIKOTA MEDAN) - Sembiring, Yan Christin Br; Parhusip, Poltak T.; Sembiring, Sabeth; Valensia, Feby (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to determine the implementation of additional income policies based on workload in the city of Medan using qualitative research through a descriptive approach. Data collection was carried out by the authors by means of document analysis, interviews, and observation. This research found the fact the provision of income addition was based in workload instead of a work achievement of goverment employees, accused the income addition policy in Medan City was not implemented well. One of some goals of income addition policy is to inerease the performance of government employees. In order to achieve that goal the goverment of Medan city should measure not only a level of job position and percentage of presence, but also an employees performance objective. Application of the additional income in the City of Medan was supposed to adjust to the minister No. 77 of 2020 and regulation on the matter of state apparatus utilization and bureaucratic reform of the republic of Indonesia No 1 of 2020 so that in determining the provisions and the provosions of addtional income does not happen confusion. In additon in implementing the goverment additional income based on workload should be the first to all civil servants, so that civil servants more prepared in the work policy. It can be done by the way obliges the head SKPD to socilize again the additional income based on workload that they have received before. In order for the purpose of the policy establishment can also be done by civil servants are required to be out in front of the SKPD. Therefore, the head SKPD have to come early before the civil servants other. It can also cause the supervision by the head SKPD.